Geografski elementi regionalnega razvoja Spodnjega Podravja s Prlekijo - Pak, Mirko (Geografski vestnik, 1996)
The presentation of situation through the problems of developmental possibilities of the region enhances the geographical and related transport position, economic lag, exceptional natural diversity and dense settling of the landscape in the influential areas of Maribor and local centres. How to activate the social and natural potentials in this polyfunctional, though mainly agrarian landscape, and concurrently conserve its natural potentials, was the basic question of the 17th assembly of Slovenian geographers at Ptuj.
Keywords: agriculture; družbena geografija; human geography; industrija; kmetijstvo; Podravje; prebivalstvo; Prlekija; prostorski razvoj; regionalni razvoj; tourism; turizem; urbanizacija